Immediate effect of warm-up on single-leg balance in individuals with and without functional ankle instability - Abalos, E.; Hung, Y.-J. (International Journal of Exercise Science, 2022)
Ankle sprains account for about 20% of all sports injuries in the United States. About 5-10 minutes of general warm-up is recommended to enhance performance and reduce injuries. However, its immediate impact on single-leg balance is unclear. The purpose of the study was to examine if different warm-up protocols could impact single-leg balance in individuals with and without functional ankle instability. Thirty volunteers (aged 19-29 years) participated in the study. The Cumberland Ankle Instability Tool was used to examine functional ankle stability and the Athletic Single-leg Stability Test of the Biodex Balance System was used to examine single-leg balance. Subjects were examined in three separate sessions (no warm-up, 5-minute warm-up, or 10-minute warm-up) with one week apart. Results show warm-up conditions had a significant impact on single-leg balance (p = .021). Pairwise comparisons showed the balance after the 5-minute warm-up was significantly worse than the no warm-up condition (p = .000). It is possible that warm-up makes the tissues surrounding lower extremity joints more flexible, therefore making single-leg balance control more challenging. In addition, subjects with functional ankle instability exhibited significantly worse single-leg balance than those without functional ankle instability (p = .003). However, the immediate effect of warm-up on balance control was similar between individuals with and without functional ankle instability. Clinicians should consider implementing single-leg balance testing and training for those who are identified as having functional ankle instability. Despite its known benefits of enhancing performance and reducing injuries, general warm-up activities may have an immediately negative effect on single-leg balance control.